Let x be the unknown number
2x +7 = 39
2x+7-7 = 39-7
2x = 32
2x/2 = 32/2
x=16
You use the balance method to solve. First, you cancel the +7 by subtracting the 7 ON BOTH SIDES to balance the equation.. After that, you are left with 2x, where you will need to isolate the x by dividing by 2 ON BOTH SIDES to balance it.
Hope this helps
Answer:
- 2x² + 7x + 1
Step-by-step explanation:
f(x) - g(x)
= x² + 2x - 6 - (3x² - 5x - 7) ← distribute parenthesis by - 1
= x² + 2x - 6 - 3x² + 5x + 7 ← collect like terms
= - 2x² + 7x + 1
B) False
Because the negation makes it opposite of what is was.
1.75, 2.75, 4
hope this helps!